2003
DOI: 10.1536/jhj.44.681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spironolactone and Metoprolol on QT Dispersion in Heart Failere

Abstract: SUMMARYThe effects of spironolactone or metoprolol added to a conventional treatment protocol on QT dispersion, which is accepted as a sudden cardiac death predictor, were evaluated in heart failure patients.?A total of 105 New York Heart Association class III patients were included in this study. The conventional treatment protocol was standardized by giving ramipril, furosemide, and digoxin to all patients for 3 weeks at the same doses. At the end of this period, the patients were divided into three groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Six trials enrolling 11654 patients reported data on SCD and CV mortality, 11, 12,25–27 and 7 trials enrolling 11826 patients reported data on total mortality. 11,12,2426,28,29 TWO trials met criteria for poor methodological quality, 27,28 and the other 6 trials met criteria for good quality (Table I in the online-only Data Supplement for quality assessment data for the trials). The Eplerenone Postacute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHESUS) trial accounted for more than half of the patients for this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Six trials enrolling 11654 patients reported data on SCD and CV mortality, 11, 12,25–27 and 7 trials enrolling 11826 patients reported data on total mortality. 11,12,2426,28,29 TWO trials met criteria for poor methodological quality, 27,28 and the other 6 trials met criteria for good quality (Table I in the online-only Data Supplement for quality assessment data for the trials). The Eplerenone Postacute Myocardial Infarction Heart Failure Efficacy and Survival Study (EPHESUS) trial accounted for more than half of the patients for this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic mineralocorticoid fludrocortisone exacerbates 37 while spironolactone improves 38,39 electrophysiological parameters such as QT interval dispersion. Spironolactone increases heart rate variability 38,40 and decreases PVBs and nonsustained VT episode occurrence 41,42 in patients with heart failure at rest and during exercise 42 ; consistent with these observations, cardiac hMR overexpression, as reported here, reduced HRV and increased PVB and nonsustained VT episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Spironolactone reduces QT parameters in patients with heart failure [17,49], and interestingly has maximum effect on these parameters in the morning when both aldosterone and sympathetic activity are rising. Unfortunately it is difficult to discern how much of the benefit of spironolactone is due to the alterations in electrolytes that it produces [43].…”
Section: Qt Intervalmentioning
confidence: 98%